2017
DOI: 10.1371/journal.pmed.1002362
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adiposity and risk of type 1 diabetes: A Mendelian randomization study

Abstract: BackgroundThe incidence of type 1 diabetes (T1D) is increasing globally. One hypothesis is that increasing childhood obesity rates may explain part of this increase, but, as T1D is rare, intervention studies are challenging to perform. The aim of this study was to assess this hypothesis with a Mendelian randomization approach that uses genetic variants as instrumental variables to test for causal associations.Methods and findingsWe created a genetic instrument of 23 single nucleotide polymorphisms (SNPs) assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 55 publications
5
71
0
Order By: Relevance
“…In a recent study based on Swedish data, we showed that sweetened beverage consumption may also increase the risk of latent autoimmune diabetes in adults (LADA) [3]. One proposed mechanism for its association with diabetes is that high consumption of sweetened beverages may lead to excess energy intake resulting in increased BMI [4], which in turn is a strong risk factor not only for T2D [5], but also for autoimmune diabetes [6,7]. However, high BMI does not seem to fully explain the associations [1,3]; there may also be direct effects on glucose metabolism including increased insulin resistance [8] and induced beta cell apoptosis [9].…”
Section: Introductionmentioning
confidence: 97%
“…In a recent study based on Swedish data, we showed that sweetened beverage consumption may also increase the risk of latent autoimmune diabetes in adults (LADA) [3]. One proposed mechanism for its association with diabetes is that high consumption of sweetened beverages may lead to excess energy intake resulting in increased BMI [4], which in turn is a strong risk factor not only for T2D [5], but also for autoimmune diabetes [6,7]. However, high BMI does not seem to fully explain the associations [1,3]; there may also be direct effects on glucose metabolism including increased insulin resistance [8] and induced beta cell apoptosis [9].…”
Section: Introductionmentioning
confidence: 97%
“…To disentangle the causal associations between DNAm and T1D risk, we employed the principles of Mendelian Randomization (MR), which is a powerful technique that has been used in both basic and clinical research [16][17][18][19][20]. Since genotypes are randomly determined at conception and not influenced by environmental confounders [21], they can be used as instruments to proxy exposures that are potentially influencing a trait, thereby mimicking a randomised controlled trial [22].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a severe medical problem and a heavy burden on people's health and their families worldwide, as well as being considered one of the major risk factors for noncommunicable diseases [1,2]. Increasing evidence has indicated that an increasing number of children are becoming obese because of overeating and overnutrition, which directly leads to various chronic diseases, such as hypertension, coronary heart disease, and type 2 diabetes (T2D) [3][4][5]. The obesity of an individual is usually evaluated by the body mass index (BMI), which is calculated by dividing the weight (BW) in kilograms by the height in meters squared, and if an individual's BMI is 30 kg/m 2 , the individual is considered obese.…”
mentioning
confidence: 99%